2024
DOI: 10.1007/s00392-023-02363-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-time cardiovascular magnetic resonance imaging for non-invasive characterisation of heart failure with preserved ejection fraction: final outcomes of the HFpEF stress trial

Sören J. Backhaus,
Alexander Schulz,
Torben Lange
et al.

Abstract: Background The diagnosis of heart failure with preserved ejection fraction (HFpEF) remains challenging. Recently, the HFpEF Stress Trial demonstrated feasibility and accuracy of non-invasive cardiovascular magnetic resonance (CMR) real-time (RT) exercise-stress atrial function imaging for early identification of HFpEF. However, no outcome data have yet been presented. Methods The HFpEF Stress Trial (DZHK-17) prospectively recruited 75 patients with dyspnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…While the need for invasive measurements of the CO can be dismissed using CMR, it might not necessarily become the standard of care, as the effort for the calculation of a simple parameter does not justify the conduction of a whole CMR scan. However, especially in HFpEF patients, CMR can provide important additional information for diagnosis and prognostication [ 9 , 29 , 30 , 31 ] and is being recommended for further evaluation diseases pathogenesis [ 32 ]. In these specific clinical indications, real-time rest and exercise stress calculation of the cardiac index can now provide additional reliable, and clinically useful information while avoiding unnecessary invasive procedures at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…While the need for invasive measurements of the CO can be dismissed using CMR, it might not necessarily become the standard of care, as the effort for the calculation of a simple parameter does not justify the conduction of a whole CMR scan. However, especially in HFpEF patients, CMR can provide important additional information for diagnosis and prognostication [ 9 , 29 , 30 , 31 ] and is being recommended for further evaluation diseases pathogenesis [ 32 ]. In these specific clinical indications, real-time rest and exercise stress calculation of the cardiac index can now provide additional reliable, and clinically useful information while avoiding unnecessary invasive procedures at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…The HFpEF-Stress trial identified changes in atrial longitudinal deformation, a functional parameter for atrial dysfunction, as highly predictive of LVFP and out-of-proportion increases in response to exercise-stress [15] . Indeed, atrial longitudinal deformation as a diagnostic and prognostic marker has come to the fore in an array of cardiovascular disease [15] , [24] , [25] , [26] , [27] . Hence, atrial function rather than size might more dynamically reflect changes in PCWP caused by exercise-stress induced congestion.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial adipose tissue (EAT) has emerged as an important risk factor in multiple diseases, while it seems to accelerate cardiac functional deterioration and increase the probability of adverse events. 1 , 2 , 3 , 4 Studies revealed that patients with increased EAT show haemodynamic alterations with functional impairment of both ventricles, as well as increased cardiac filling pressures at rest and during exercise stress with concomitantly reduced exercise capacity. 5 , 6 , 7 , 8 Furthermore, EAT directly impacts local cardiac structure 4 and is suspected to cause inflammation and remodelling, both playing a role in the development and progression of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%